Identifikasi Keluhan Computer Vision Syndrome (CVS) Pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Sonia Fillani Indah; Ni Wayan Winianti; Ni Wayan Sedani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Computer Vision Syndrome (CVS) is a collection of symptoms in the eyes and neck caused by excessive use of computers or monitors. Complaints of CVS become a health problem that needs attention because it can reduce productivity and quality of life in the future. The purpose of this study was to determine the most common CVS and CVS complaints among medical students at the Faculty of Medicine and Health Sciences, University of Warmadewa (FKIK Unwar) based on the identification carried out. This research is a descriptive observational study with a cross sectional research design. The study was conducted at FKIK Unwar with a sample of 123 people in January 2022. Data were obtained by filling out online questionnaires and interviews and then univariate analysis. The results showed that the most common complaint of asthenopia symptoms was eye fatigue 101 respondents (82.1%). On the symptoms on the ocular surface, the most common complaint is watery eyes with a frequency of 56 respondents (45.5%). In visual symptoms, the most common complaint is sensitivity to light with a frequency of 64 respondents (52%) and in esctarocular symptoms the most common complaint is back pain with a respondent frequency of 80 people (65%). The conclusion in this study is that the most common CVS complaints felt by FKIK Unwar students were asthenopia symptoms with complaints of tired eyes with a respondent frequency of 101 people (82.1%) and visual symptoms with complaints of double vision were the complaints that were most rarely felt by FKIK Unwar students with a frequency of respondents 15 people (12.2%)